Pendidikan Multikultural dalam Tradisi Pesantren di Yogyakarta - Listiyono Santoso, et al. (Islamica: Jurnal Studi Keislaman, 2012)
This study discusses the concept of multiculturalism according to the santris and its relation to their religiosity. Santris are those who study at the pesantren, the indigenous form of education in Indonesia. The paper offers a descriptive elaboration of what these santris think of multiculturalism and how they relate it to their belief and religious tradition. It argues that multiculturalism has been the very character of the pesantren in which santris of various cultural background stay to study. How thismulticulturalism works and how it influences the santris in the way they look at the idea of nation-hood is the question that needs to be explored. And this paper aims at doing just that. Nation-hood is just another form of multiculturalism. While the santris are used to a life of a multicultural nature, the question of how they adapt to the national culture on the one hand, and how religion shapes the way they behave on the other becomes of particular interest. This paper will show that religion and nationalism are two sides of the same coin?as it were?in the life of the santris.